A wood–polypyrrole composite as a photothermal conversion device for solar evaporation enhancement. Issue 36 (27th August 2019) - Wang, Zhe; Yan, Yutao; Shen, Xiaoping; Jin, Chunde; Sun, Qingfeng; Li, Huiqiao
Abstract : A wood–polypyrrole composite as a photothermal conversion device for efficient seawater desalination and water purification. Abstract : Wood is gaining increasing attention in applications related to solar steam generation because of its porous structure with microchannels, low heat conduction properties, highly hydrophilic properties and renewability. Wood surface modification is required to improve steam generation performance because of its low optical absorptivity. Unfortunately, the high energy consumption fabrication process and high cost of current photothermal conversion coatings on wood impede its large-scale application. This study develops a facile pyrrole polymerization method to acquire polypyrrole decorated wood (PPy–wood) for solar evaporation enhancement. The black PPy decoration considerably improves the wood light absorption, resulting in a high absorbance (>90%) of PPy–wood within a broad wavelength range, from the ultraviolet region to the near infrared region (300–2500 nm). The combination of advantages related to wood (microchanneled porous structure, high hydrophilicity and thermal insulation) and PPy (broadband and high solar absorption capacity) for easy and fast steam generation makes PPy–wood an ideal solar steam generator, which shows rapid evaporation abilities (1.014 kg m −2 h −1 ) and high evaporation efficiency (72.5%) under simulated one sun irradiation. Moreover, the obtained clean water using PPy–wood as the steam generator shows low ion concentrations and high transmittance, demonstrating that PPy–wood possesses excellent potential for seawater desalination and sewage treatment. Thus, such PPy–wood is a potential candidate for water desalination and purification to address water scarcity issues through the effective utilization of clean energy.